2011
DOI: 10.1371/journal.pone.0019581
|View full text |Cite
|
Sign up to set email alerts
|

Structure Collisions between Interacting Proteins

Abstract: Protein-protein interactions take place at defined binding interfaces. One protein may bind two or more proteins at different interfaces at the same time. So far it has been commonly accepted that non-overlapping interfaces allow a given protein to bind other proteins simultaneously while no collisions occur between the binding protein structures. To test this assumption, we performed a comprehensive analysis of structural protein interactions to detect potential collisions. Our results did not indicate cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The rotation angle between EC1 (chain A) and EC1 (chain B) in the strand-swap dimer was calculated with DynDom45. Overlapping volumes were evaluated with MSMS of the CHIMERA suite4647.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotation angle between EC1 (chain A) and EC1 (chain B) in the strand-swap dimer was calculated with DynDom45. Overlapping volumes were evaluated with MSMS of the CHIMERA suite4647.…”
Section: Methodsmentioning
confidence: 99%
“…The region where two molecules of TSP7 clash with each other when P-cadherin adopts the X-dimer conformation is highlighted with a dotted line. The overlapping volume was calculated with MSMS46. (e) Binding isotherm of P-cadherin constructs (EC12 K14E, MEC12, or MEC12 K14E) to TSP7.…”
Section: Figurementioning
confidence: 99%
“…It has been found that separate binding interfaces might not imply simultaneously possible protein interactions [27]. For a given host protein, two binding partners might collide in 3-D space although their binding sites are not overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that separate binding interfaces might not imply Table 5 The impact of the selection of the threshold of defining hubs with multi interfaces simultaneously possible protein interactions [19]. For a given host protein, two binding partners might collide in 3D space although their binding sits are not overlapping.…”
Section: Discussionmentioning
confidence: 99%